The impact of innovation in promotion on consumer purchasing decision-making : a study on consumers of the ready-made clothing market in the city of Lattakia) (Journal of Hama University, 2025)
Innovation is a real, comprehensive requirement for all sectors in various fields, as the need of companies must be translated into their desire to develop and continue in light of the changes and changing circumstances they face in the tastes of their customers, by presenting and promoting their products with various elements and the latest innovative methods and methods, with the goal of keeping pace with media and information technology.And in keeping with the tremendous progress, the study focused on determining the impact of innovation in the field of promotion adopted by ready-made clothing companies and stores in the Lattakia markets, on purchasing decision-making among consumers of the target clothing market. It adopted a descriptive analysis approach, and distributed a questionnaire estimated at 330. A customer from the previous market, and the results summarized that there was a noticeable average evaluation regarding the reality of innovation in the field of promotion, and it was not to the desired degree from the point of view of these individuals, and that there was a weak evaluation regarding making the decision related to purchasing, and a weakness in the desire formed to try the promoted products, It also became clear that there was an average correlation of 26.9%, and a specific, fundamental effect, that an increase of one degree in the innovations used in the field of promotion would be followed by an increase of 0.238 degrees in consumer decision-making, and that the influence of university consumers on their decisions was to a higher degree compared to the rest of the categories. Regarding the level of education
Keywords: : “Innovation in Promotion”